2021
DOI: 10.3389/fnagi.2021.706609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dance Interventions on Cognition, Psycho-Behavioral Symptoms, Motor Functions, and Quality of Life in Older Adult Patients With Mild Cognitive Impairment: A Meta-Analysis and Systematic Review

Abstract: Background: Dance interventions are considered beneficial for older patients with mild cognitive impairment in many aspects. We conducted a comprehensive systematic review and meta-analysis to assess the effects of dance on different aspects (cognitive function, emotions, physical function, and quality of life) of this population.Methods: A systematic search of PubMed, Web of Science, the Cochrane Central Register of Controlled Trials, Embase, American Psychological Association PsycInfo, ProQuest, Scopus, Cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
3
14
0
Order By: Relevance
“…The Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and Function and Cognitive Assessment Test (FUCAS) were used to assess the global cognitive level of MCI patients. Three high-quality systemic and meta-analysis studies (Chan et al, 2020 ; Liu et al, 2021 ; Wu et al, 2021 ) reported that global cognitive function remarkably increased when older adults with MCI practiced dance compared with the control group [Wu et al ( 2021 ), SMD = 0.54, Z = 3.55, p < 0.001; Liu et al ( 2021 ), SMD = 0.73, 95%CI = 0.47 to 0.99, p < 0.001; Chan et al ( 2020 ), SMD = 0.48, 95%CI = 0.21 to 0.74]. The meta-analysis results of Wu et al ( 2021 ) showed that the efficacy of DMT on the MMSE is related to the overall duration of intervention.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and Function and Cognitive Assessment Test (FUCAS) were used to assess the global cognitive level of MCI patients. Three high-quality systemic and meta-analysis studies (Chan et al, 2020 ; Liu et al, 2021 ; Wu et al, 2021 ) reported that global cognitive function remarkably increased when older adults with MCI practiced dance compared with the control group [Wu et al ( 2021 ), SMD = 0.54, Z = 3.55, p < 0.001; Liu et al ( 2021 ), SMD = 0.73, 95%CI = 0.47 to 0.99, p < 0.001; Chan et al ( 2020 ), SMD = 0.48, 95%CI = 0.21 to 0.74]. The meta-analysis results of Wu et al ( 2021 ) showed that the efficacy of DMT on the MMSE is related to the overall duration of intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The Verbal Fluency F-A-S Test (FAS) and Mississippi Aphasia Screening Test (MAST) are the commonly used language-cognition assessment tools. The results of three meta-analyses demonstrated that DMT positively enhances the verbal fluency in MCI patients (Liu et al, 2021 ; Wu et al, 2021 ). Two meta-analyses confirmed that DMT can improve in the visuospatial function of patients with MCI (Chan et al, 2020 ; Wu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations